(untitled) (Revista Linhas, 2018)
Taking into consideration a discussion on the relationship between religion and education in a laic country, and possible consequences of such relationship for society (DUARTE and NETO, 2013; EMMERICK, 2010; HAGOPIAN, 2006; MENDONÇA, 1995), this bibliographic paper aims at investigating possible effects or consequences of religion on education in Brazil. For such purposes, a literature review was conducted, resulting in 13 studies. The Meta-analysis approach (GLASS, MCGAW, SMITH, 1981) was adopted for data analysis. Results reveal that schools still perpetuate and legitimize a catholic discourse. Moreover, religion has proven to influence decision-making, self-esteem, academic performance and other issues. Keywords: Religion. Education. Brazilian Context.